2021
DOI: 10.1111/jfbc.13649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different preheat treatments on volatile compounds of camellia ( Camellia oleifera Abel .) seed oil and formation mechanism of key aroma compounds

Abstract: Camellia oleifera (Camellia oleifera Abel.), which belongs to Theaceae, is an endemic woody edible oil tree species in China, and it is also one of the four major woody oil crops in the world (Liang et al., 2017). Camellia seed oil (CSO) is a vegetable oil extracted from camellia seeds, which fatty acid composition and physical and chemical properties are very similar to olive oil, so it is known as "Oriental Olive Oil" (Zhu et al., 2020). It is rich in monounsaturated fatty acids and a variety of functional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…It is particularly noteworthy that they are all aldehydes and the specific reason for this occurrence pattern remains to be determined. Hexanal was also a common compound of aldehydes and found in 19 VCO samples, which is consistent with the previous research [ 38 , 42 ]. It is produced by linoleic acid oxidation and shows high content in tea seed oil, grape seed oil, soybean oil, and corn oil [ 34 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…It is particularly noteworthy that they are all aldehydes and the specific reason for this occurrence pattern remains to be determined. Hexanal was also a common compound of aldehydes and found in 19 VCO samples, which is consistent with the previous research [ 38 , 42 ]. It is produced by linoleic acid oxidation and shows high content in tea seed oil, grape seed oil, soybean oil, and corn oil [ 34 ].…”
Section: Resultssupporting
confidence: 92%
“…Among them, ketones (69) were the most abundant volatile compounds in this study ( Figure 2 A); these are formed by auto-oxidation of fatty acids, β-oxidation, and decarboxylation [ 39 ], and usually give the sweet and fruity flavor. Alcohols (57) and aldehydes (48), also as main compounds in all VCO samples, being formed by oxidative degradation of fatty acids or Strecker degradation of amino acids [ 38 ], contributed the overall odor of Camellia oil with large quantity; these findings are consistent with a previous report [ 34 ]. A total of 51 esters were identified that can be produced by esterification of alcohols with free small molecular fatty acids, or by enzymatic degradation of amino acids during the growth of Camellia oleifera .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…UPR is applied to analyze the overall structure of data without grouping samples, and it includes principal component analysis (PCA) and hierarchical cluster analysis (HCA). PCA is a multivariate statistical analysis in which multidimensional data is transformed into several important variables, namely principal components, and projects datas into 2- or 3-D space; a principal component score graph facilitates the exhibition of data distribution and analysis of data aggregation and dispersion ( He et al, 2021 ). HCA aggregates similar data into one cluster, whereas different data into different clusters.…”
Section: Lipidomicsmentioning
confidence: 99%